The Sero-Prevalence of Hepatitis B and C Viruses in Municipal Waste Collectors in Southwest of Iran - Sarvari, Jamal; Joharinia, Negar; Shiri, Alireza; Vali, Atefeh; Beigzadeh, Farshid; Davarpanah, Mohammad Ali; Atapour, Amir; Khoshbakht, Rohollah; Jaberi, Omid; Hosseini, Seyed Younes (Indian journal of occupational and environmental medicine, 2023)
Aims: The present study aimed to investigate the frequency of hepatitis B virus (HBV) and hepatitis C virus (HCV) serological markers among waste collectors in the municipality of Shiraz city, southwest of Iran, 2018. Settings and Design: In this cross-sectional study, a total of 385 waste collectors from all 10 districts of Shiraz city, southwest of Iran were enrolled. A questionnaire was used to gather occupational and demographic information as well as awareness about viral hepatitis. Methods and Material: Their blood samples were collected, and the sera were investigated for the presence of hepatitis B surface antigen (HBsAg), anti-HBs antibody, and anti-HCV antibody using enzyme-linked immunosorbent assay (ELISA). Results: All the participants were men with a mean age of 41 ± 8 years. Out of 385 participants, 6 (1.5%) subjects were positive for HBsAg, indicative of HBV infection. Moreover, 38 (9.9%) had a protective level of anti-HBs antibodies, while more than 90% had a low level of anti-HBs antibodies. All participants were negative for HCV antibodies. Conclusion: According to these findings, evaluation of HBsAg and anti-HBs levels is recommended in the healthy program of waste collector workers (WCWs). However, this occupation might not be a risk factor for the acquisition of HBV and especially HCV infections.